2021
DOI: 10.3390/cancers13194878
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Care for Adult Cancer Patients: Guidelines of the Italian Medical Oncology Association

Abstract: Psychosocial morbidity can have negative consequences for cancer patients, including maladaptive coping, poor treatment adherence, and lower quality of life. Evidence shows that psychosocial interventions can positively impact quality of life, as well as symptoms and side effects; however, they are not always offered to patients who might benefit from them. These guidelines were produced by a multidisciplinary panel of 16 experts, including patients, following GRADE methodology. The panel framed clinical quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Given that the existing evidence of the effectiveness of reminiscence‐based interventions for caregivers is very limited, future interventions that consider caregivers and patients as a whole can be designed to explore the effectiveness of reminiscence‐based interventions for caregivers (Wang et al., 2021; Yang et al., 2023). Finally, we found that people whose physical function or spatial distance does not support face‐to‐face traditional interventions may not benefit from reminiscence‐based interventions, which may limit the wider use of reminiscence‐based interventions to some extent (Bakitas et al., 2021; Caminiti et al., 2023). Therefore, the mobility and convenience of the new Internet communication technology may compensate for the shortcomings of the traditional reminiscence‐based intervention and provide the possibility to solve the space–time distance.…”
Section: Discussionmentioning
confidence: 91%
“…Given that the existing evidence of the effectiveness of reminiscence‐based interventions for caregivers is very limited, future interventions that consider caregivers and patients as a whole can be designed to explore the effectiveness of reminiscence‐based interventions for caregivers (Wang et al., 2021; Yang et al., 2023). Finally, we found that people whose physical function or spatial distance does not support face‐to‐face traditional interventions may not benefit from reminiscence‐based interventions, which may limit the wider use of reminiscence‐based interventions to some extent (Bakitas et al., 2021; Caminiti et al., 2023). Therefore, the mobility and convenience of the new Internet communication technology may compensate for the shortcomings of the traditional reminiscence‐based intervention and provide the possibility to solve the space–time distance.…”
Section: Discussionmentioning
confidence: 91%
“…In-person appointments were reported to be more common than were virtual appointments. While in-person care has been viewed as the "gold standard" for patient-physician interaction, virtual care, such as telemedicine, can help overcome the challenge of geographical distance for patients in remote or rural regions and reduce anxiety amongst cancer patients [26,27]. In one study, it was found that replacing traditional in-person care with technology-based remote options can lead to improvement in the psychosocial health outcomes (e.g., anxiety, depression,) associated with cancer diagnosis and treatment [27].…”
Section: Discussionmentioning
confidence: 99%
“…The idea for this research is based on the work of the Panel for the Guidelines on the Psychosocial Care for Adult Cancer Patients, published by the Italian Association of Medical Oncology (AIOM) annually since 2012 [ 29 ]. In light of the unprecedented rise in virtual care in oncology following COVID-19, the panel decided to investigate the psychosocial impact of new forms of technology-based distance care, in order to include corresponding recommendations in the next guideline update.…”
Section: Methodsmentioning
confidence: 99%